Contrast-Induced Encephalopathy After Endovascular Thrombectomy for Acute Ischemic Stroke. Issue 12 (December 2020) - Chu, Yung-Tsai; Lee, Kang-Po; Chen, Chih-Hao; Sung, Pi-Shan; Lin, Yen-Heng; Lee, Chung-Wei; Tsai, Li-Kai; Tang, Sung-Chun; Jeng, Jiann-Shing
Abstract : Background and Purpose: Contrast-induced encephalopathy (CIE) is a rare and underrecognized complication after endovascular thrombectomy (EVT) for acute ischemic stroke. This study investigated the incidence and risk factors of CIE in patients who underwent EVT. Methods: Consecutive patients with acute ischemic stroke who received EVT between September 2014 and December 2019 at 2 medical centers were included. CIE was diagnosed on clinical criteria of neurological deterioration or delayed improvement within 24 hours after the procedure that was unexplained by the infarct or hemorrhagic transformation and radiological criterion of edematous change extending beyond the infarct core accompanied by contrast staining. Results: Of 421 patients with acute ischemic stroke who received EVT, 7 (1.7%) developed CIE. The manifestations included worsening of focal neurological signs, coma, and seizure. Patients with CIE were more likely to experience contrast-induced acute kidney injury than were those without CIE, but the volume of contrast medium was comparable between the two groups. The independent risk factors for CIE included renal dysfunction (defined as an estimated glomerular filtration rate <45 mL/min per 1.73 m 2 ; odds ratio, 5.77 [95% CI, 1.37–24.3]; P =0.02) and history of stroke (odds ratio, 4.96 [95% CI, 1.15–21.3]; P =0.03). Patients with CIE were less likely to achieve favorable functional outcomes (odds ratio, 0.09 [95% CI, 0.01–0.87]; P =0.04). Conclusions: CIE should be suspected in patients with clinical worsening after EVT accompanied by imaging evidence of contrast staining and edematous changes, especially in patients with renal dysfunction or history of stroke. Abstract : Supplemental Digital Content is available in the text.